Validity and reliability test of NIHSS-SDKI and CNS-SDKI in determining actual nursing diagnosis and severity of stroke patients - Erlis Eka Fitriana; Haryanto Haryanto; Supriyadi Supriyadi (Medisains)
Background: The National Institutes of Health Stroke Scale (NIHSS) and The Canadian Neurological Stroke Scale (CNS) are two assessment tools often used for the assessment of neurological status in stroke patients. However, there are no assessment tools that use the standard nursing diagnoses developed in Indonesia, namely the Standar Diagnosis Keperawatan Indonesia (SDKI),  developed by the Indonesian National Nurses Association organization.